Chicken Soup By Heart - Hershenhorn, Esther (New York, 2002)
When Rudie's sitter gets the flu, he uses her recipe to make her a batch of special chicken soup, including the secret recipe of stories from the heart.
Keywords: Jews; Fiction; Sick; Babysitters; Soups; Fiction; Fiction; Fiction